2017
DOI: 10.1002/jmv.24800
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and phylogenetic investigation for a nosocomial outbreak of respiratory syncytial virus infection in an adult hemato‐oncology unit

Abstract: Although many reports have already shown RSV outbreaks among hemato-oncology patients, genomic studies detecting similar RSV strains prior to an outbreak in the hospital are rare. In 2014, the University of the Ryukyus hospital hemato-oncology unit experienced, and successfully managed, a respiratory syncytial virus (RSV) nosocomial outbreak. During the outbreak investigation, genotyping and phylogenetic analysis was used to identify a potential source for the outbreak. Nasopharyngeal swabs were tested for RSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Among the most commonly detected viral pathogens, RSV was prevalent in respiratory swab of paediatric patients and nearby surfaces. RSV has been a major nosocomial hazard on pediatric wards and has been linked with hospital outbreaks [31, 32]. With reported higher case fatality among patient with nosocomial RSV infections (OR 4.46, 95% CI 1.1–18), widespread surface contamination with RSV is concerning for low income hospitals (34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…Among the most commonly detected viral pathogens, RSV was prevalent in respiratory swab of paediatric patients and nearby surfaces. RSV has been a major nosocomial hazard on pediatric wards and has been linked with hospital outbreaks [31, 32]. With reported higher case fatality among patient with nosocomial RSV infections (OR 4.46, 95% CI 1.1–18), widespread surface contamination with RSV is concerning for low income hospitals (34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular characterization of RSV strains, for instance by whole genome sequencing [37] or characterization of RSV G-Protein [16,38], has been used to investigate nosocomial RSV outbreaks. We were able to collect and examine selected outbreak strains by G-Protein gene sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, hospital (nosocomial) acquisition is possible as well and transmission may occur by other infected patients, staff or visitors [11,12]. RSV outbreaks in inpatient pediatric oncologic care facilities and in adult hematology and oncology units have been described [9,[12][13][14][15][16]]. An understanding of transmission pathways helps to guide adequate outbreak control measures and to implement prophylactic measures.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis by Cochrane showed that the spread of respiratory viruses can be prevented by hygienic measures, such as barrier precautions and hand washing . Different modalities of isolation by viruses are portrayed in Table , including current recommendations by the American Society of Blood and Marrow Transplantation guidelines and standard practices at our own institution. Emerging data regarding enhanced isolation precautions, including contact and droplet precautions for all respiratory viruses, showed a 39% reduction in nosocomial infections .…”
Section: Preventing Infectionmentioning
confidence: 99%